Adsorptive and Membrane-Type Separations: A Bibliographical Update (1999) - Martyn S. Ray (Adsorption Science & Technology)
This paper provides a useful and quick reference source to the 1999 journal literature on adsorptive and membrane-type separations (from the 50 most important chemical engineering journals) for researchers in this area. This article continues a series of annual bibliographic updates of the literature published since 1985 (see Ray 1990–1999). The references included here have been divided into the following subject groups: theory; design data; adsorbents; PSA and cyclic systems, and applications; liquid-phase adsorption; ion exchange, chromatography and related separations; membranes; and membrane-type separations. Adsorption and related separations for industrial and environmental applications are described in detail by Dabrowski (1999) which also contains extensive bibliographies prepared by this author. A complete bibliographic listing of the chemical engineering journal literature from 1959 to 1999 (with subsequent six-monthly updates) is available on a CD-ROM database* and full details can be obtained from the author.